Different creep compound feed formulations for new born piglets: influence on growth performance and health parameters - Badaras, Sarunas; Ruzauskas, Modestas; Gruzauskas, Romas; Zokaityte, Egle; Starkute, Vytaute; Klupsaite, Dovile; Mockus, Ernestas; Klementaviciute, Jolita; Vadopalas, Laurynas; Zokaityte, Gintare; Dauksiene, Agila; Bartkevics, Vadims; et al. (Frontiers in Veterinary Science, 2022)
The aim of this study was to compare the influence of different compositions of creep compound feed (CCF) (C-I – control group; TG-II – a CCF containing wheat bran extruded and fermented with L. paracasei; TG-III – a creep compound feed containing sugar beet pulp) on the faecal microbial profile and physicochemical char-acteristics, blood parameters and growth performance in piglets. Moreover, the faecal volatile compound (VC) profile was analysed as a possible chemical marker related to changes in the faecal microbial profile and physi-cochemical characteristics. A 21-day experiment was conducted using 1-day-old 300 Large White/Norwegian Landrace piglets. At the end of the experiment, significantly higher lactobacillus counts in the faeces of both treated groups were found, and a correlation between faecal textural hardness and the lacto-bacillus count was established (r = 0.475). Significant correlations of piglets’ individual faecal VC with mi-crobiological parameters and faecal pH were established (lactobacilli with 3-n-nonadecanol-1; enterobacteria with butyric acid<2-methyl->; pentanoic acid, 4-methyl-; eicosene(E)-, etc.). The highest body weight (at the 21st day) was found in piglets of the TG-III group, and both treated groups showed lower feed conversion ratios. It can be concluded that local material could be successfully incorporated into CCF preparation without impairing animal metabolism.